2012
DOI: 10.18052/www.scipress.com/bsmass.3.28
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Inductive Inquiry and Transmitter of Knowledge Models on Secondary School Students’ Achievement on Circle Geometry and Trigonometry

Abstract: In this study, the effectiveness of Inductive Inquiry and Transmitter of Knowledge models on students’ academic achievement on Circle Geometry and Trigonometry is explored. The main objectives of the study are to expose the groups to Inductive Inquiry and Transmitter of Knowledge models and compare the effectiveness of these modes of teaching in the teaching of circle geometry and trigonometry. The pre-test-post-test experimental design is chosen for this work. It is hypothesized that there would be significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…While the inductive approach was appropriate to be applied in the second material, the Kinetic Theory. The results of previous research found that the learning process using both inductive and deductive approach did not show any significantly different results in the short answers and multiple-choice questions (Ihedioha & Osu, 2012;Lee & Park, 2013). However, in this study, it does not happen.…”
Section: Results Of Quantitative Analysis On Inductive and Deductive Acontrasting
confidence: 78%
See 1 more Smart Citation
“…While the inductive approach was appropriate to be applied in the second material, the Kinetic Theory. The results of previous research found that the learning process using both inductive and deductive approach did not show any significantly different results in the short answers and multiple-choice questions (Ihedioha & Osu, 2012;Lee & Park, 2013). However, in this study, it does not happen.…”
Section: Results Of Quantitative Analysis On Inductive and Deductive Acontrasting
confidence: 78%
“…However, the sub-material also affects the effectiveness of the application of inductive or deductive approaches. If the problem is based on experience and observation then the inductive approach will be used, meanwhile, if the material is based on certain laws, rules, and principles, the deductive approach is more effective to be applied apply (Trochim, 2006;Ihedioha & Osu, 2012). Based on the material study of international curriculum-standard, the appropriate topic in implementing deductive approach is subjects that contains the points or charts that known by students w first, such as Chemistry and Material and Material Classification.…”
Section: Results Of Quantitative Analysis On Inductive and Deductive Amentioning
confidence: 99%
“…To the former, teaching is viewed as a "performer" [41]. Ihedioha [42] describes that a knowledge transmitter "emphasizes the need to give pupils basic facts and information before they can be expected to think for themselves" (p. 36). Afterward, he argues that with this deductive model, "so much of the work of learning is controlled and directed by the teacher" (p. 37), and therefore "some students will do better under learning conditions that are fewer teachers directed and controlled" (p. 37).…”
Section: Focus On Teachers' Rolesmentioning
confidence: 99%
“…In practice, I observed sampled schools and found that they are using both inductive and deductive teaching methods unknowingly. Primary schools are at the very beginning stage of learning mathematics; at this level, most of the mathematical concepts should taught by an inductive approach (Silas & Bright, 2012). There are many researches on inductive and deductive methods, such as Shoib (2010) elementary level mathematics in Nepal.…”
Section: Introductionmentioning
confidence: 99%